DEVELOPING VOCATIONAL-BASED LEARNING MATERIALS TO WRITE SCIENTIFIC PAPERS TO IMPROVE THE POLYTECHNIC STUDENTS’ ACADEMIC WRITING SKILLS IN INDONESIAN LANGUAGE COURSE - Moh. Thamrin (Jurusan Sastra Indonesia, 2017)
This research seeks to develop vocational-based learning materials to write scientific papers, particularly tailored to improve the Polytechnic students’ academic writing skills entailed in Indonesian Language course. This research employed the combination of two modified instructional design models, namely, R2D2 (recursive, reflective, design, and development) andR&D (research and development. From the amalgamation of the two developmental models, the researcher obtained the development procedures as follows: (1) preliminary study, (2) determination, and (3) design and development. The learning materials encompass 5 learning competencies, namely, (1) writing scientific works, (2) scientific articles, (3) writing apprentice work reports, (4) writing citations and references, and (5) editing the language employed in scientific works. Those five competencies are developed in accordance with the characteristics of learning materials for Polytechnic students, namely, (1) encompassing competence on scientificworks writing; (2) installing understanding on the nature of scientific works; (3) designing or composing scientific works; (4) explicating steps required to write scientific papers as standard operating procedure (SOP); (5) practicing writing scientific papers; (6) assessing the outcomes of the practice by using instruments.